A case of treatment on temporomandibular arthrosis induced by openbite of the molar region: Examination based on waveform of occlusal sound - MASUDA, Katsumi; SHIMADA, Keikichi (Journal of the Japanese Society for the Temporomandibular Joint, 1993)
This study reports a case of temporomandibular arthrosis thought to be induced by peculiar dual bite forcing the condyle to displace forward. This resulted flom many years' continuous use of a high template incurring an openbite of the molar region. The openbite in turn induced a back-down rotation of the mandible and a backward displacement of the condyle on the right with an abnormal contact of 2:32. Thes features were noted on the removal of the appatatus. In treatment of this case, the aim from the start was to improve the two peculiar types of occlusion at the same time. Particular attention was given to adjustment of the vertical dimension of the occlusion, In order to create the proper habit of occlusion. The purpose of this was to readjust the muscular function affected by malocclusion over a long period of time. The progress of treatment for this case was followed using occlusal sound waveform to gather diagnostic data occlusal amelioration. It was confirmed that the varied abnormal waveform was corrected. Furthermore in parallel with this, such symptoms as temporomandibular pain, trismus and clicking strikingly improved as the occlusion improved. The study indicates that a close correlation exists between the restoration of the temporomandibular condyle, normalization of occlusion and the waveform of occlusal sound. Moreover, the usefulness of examination based on occlusal sound waveform was confirmed.